Berdirinya Negara di atas Negara: Sejarah Perampasan Tanah Palestina oleh Israel yang Membawa pada Pelanggaran Hak Asasi Manusia - Zhafira, Ayla (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2023)
Human Rights are given to all humans born in the world because they are human, not because positive law that applies. It is prohibited for anyone to violate human rights either intentionally or unintentionally, then there will be penalties that apply to every violation committed by both serious and minor customers. This provision also applies to anyone whose human rights have been violated as a result of the bloody conflict between Palestine and Israel. Israel’s human rights violations against Palestinians are violations of other people’s rights, especially the right to a decent and safe life. This conflict has been going on for a long time and there is no resolution yet. The longer the time spent, the greater the human rights that Palestinians are fighting for. For this reason, I carried out a historical analysis by collecting existing and relevant data and then reviewing it again. The aim of this research is to study the conflict between Palestine and Israel which resulted in human rights violations against Palestinians. Based on analysis, Israel and Palestine have long been at odds, and Israeli attacks have damaged and destroyed many homes and places of worship. Israel is believed to have committed many serious human rights violations against Palestine and this has been going on for a long time and is still happening today.